2020
DOI: 10.1111/jan.14564
|View full text |Cite
|
Sign up to set email alerts
|

The state of nursing research from 2000 to 2019: A global analysis

Abstract: Aim This study aims to present a general bibliometric overview of the development status of global nursing research from 2000 to 2019. Design A longitudinal bibliometric analysis of nursing research was conducted. Methods Nursing research publications (N = 88,665) were obtained from Web of Science. Bibliometric method was used to map the output and citation impact trends of countries/regions, institutions, disciplines, and journals and analyse the research collaboration among countries/regions and institutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 42 publications
1
17
0
2
Order By: Relevance
“…Interestingly, in terms of the number of productive authors and institutions, Canada ranked ahead of the USA. Collaborations tends to be stronger between institutions or countries with shorter geographical distances [7], and we found co-operation links between authors and institutions within Canada were stronger than that in the United States(Figure S1 and Figure 4B). Considering the scattered collaborations in this eld, we hope there will be more inter-institutions and international research in the future.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, in terms of the number of productive authors and institutions, Canada ranked ahead of the USA. Collaborations tends to be stronger between institutions or countries with shorter geographical distances [7], and we found co-operation links between authors and institutions within Canada were stronger than that in the United States(Figure S1 and Figure 4B). Considering the scattered collaborations in this eld, we hope there will be more inter-institutions and international research in the future.…”
Section: Discussionmentioning
confidence: 78%
“…A study by Yanbing et al, (2020) provides a global overview of nursing research based on a bibliometric analysis of research published between 2000–2019. This study identified 20 countries with the highest scientific output in nursing during this period.…”
Section: State Of Countries Producing Research In Nursing Sciencesmentioning
confidence: 99%
“…Taking the worldwide ranking as a reference, from the journals indexed in the Scopus/SCImago database in the 1996-2020 period, Brazil is the 1 st country in Latin America and the 8 th in the world in number of documents published in the field of Nursing, only behind the United States of America, the United Kingdom, Australia, Canada, France, Germany and Spain**. 2 Although Brazil is recognized among the 20 countries with the highest number of publications in the area, in terms of citations, such relevance is not reached 13 . This panorama is due to the fact that only three Brazilian nursing journals are indexed in the Web of Science database, a number well below the approximately 41 journals in the area 14 .…”
Section: /21mentioning
confidence: 99%